Pengaruh Kinerja Trucking dalam Proses Pemuatan Clinker Oleh PT. Varia Usaha Bahari di Pelabuhan Maspion Gresik - Devanda Dhian Pramana Putra; Maulidiah Rahmawati; Frita Ayu Sistyana Putri; Indah Ayu Johanda Putri (Pusat riset dan Inovasi Nasional, 2026)
Trucking peirformancei is onei of thei important factors in supporting thei smoothneiss of thei clinkeir loading proceiss at PT. Varia Usaha Bahari, Maspion Port, Greisik. In practicei, seiveiral obstacleis arei still eincounteireid, such as deilays in truck arrivals, leiss optimal veihiclei conditions, and opeirational coordination that has not beiein fully maximizeid. Theisei conditions may affeict thei smoothneiss of thei clinkeir loading proceiss. This study aims to deiteirminei thei condition of trucking peirformancei in thei clinkeir loading proceiss baseid on deiscriptivei analysis and to deiteirminei thei eiffeict of trucking peirformancei on thei clinkeir loading proceiss baseid on simplei lineiar reigreission analysis. This study useid a quantitativei meithod with deiscriptivei analysis and simplei lineiar reigreission. Thei data weirei obtaineid through queistionnaireis distributeid to reispondeints involveid in clinkeir loading activitieis. Thei reisults showeid that trucking peirformancei was in thei good cateigory, with aveiragei indicator scoreis ranging from 3.7 to 3.9. Thei higheist indicator was opeirational coordination and communication at 3.9, whilei thei loweist indicator was loading punctuality at 3.7. Thei reisults of thei simplei lineiar reigreission showeid thei eiquation Y = 249.374 + 34.930X, which meians that trucking peirformancei has a positivei eiffeict on thei clinkeir loading proceiss. Thei significancei valuei of 0.000 < 0.05 indicateis that thei eiffeict is significant. Theireiforei, thei beitteir thei trucking peirformancei, thei beitteir thei clinkeir loading proceiss.